THE EFFECT OF MOTIVATION, DISCIPLINE AND INFRASTRUCTURE ON PERFORMANCE OF GOVERNMENT EMPLOYEES WITH A WORK AGREEMENT (P3K) IN THE DISTRICT GOVERNMENT BARITO KUALA IN MARABAHAN CITY - Dhini Ayu Indriarti; Nurus Sjamsi (SEAN Institute, 2021)
Study This lift relatedness between motivation, discipline and means infrastructure on Employee Performance of Employees Government with Agreement Government Work (P3K) Barito Kuala Regency In Marabahan City. Object study is visitors employee with Employee status Government with Agreement Work (P3K). Retrieval technique sample used with technique taking sample is total sampling, with amount sample study as many as 142 employees whose placement is in the Department of Education and the Department of Agriculture Food Crops and Horticulture Government Barito Kuala Regency, engineering analysis used is analysis regression multiple For know influence motivation, discipline and means infrastructure on Employee Performance. From the results analysis can known that : (1) There is influence in a way simultaneous between variable motivation, discipline and means infrastructure to performance Employee Government with Agreement Government Work (P3K) Barito Kuala Regency in Marabahan City ; (2). There is influence in a way partial between variable motivation, discipline and means infrastructure to performance Employee Government with Agreement Government Work (P3K) Barito Kuala Regency in Marabahan City ; and (3). Discipline influential dominant to to performance Employee Government with Agreement Government Work (P3K) Barito Kuala Regency in Marabahan City.